ANALISIS SISTEM PERADILAN INDEPENDEN DALAM MEMBERANTAS KORUPSI DI INDONESIA - David Saputra (LPPM STISIP IMAM BONJOL, 2022)
The independent judicial system is a form of elaboration of the Indonesian state of law, and is also one of the efforts besides that it also has the potential to cause greater corruption. Where corruption has been civilized and become one of the diseases of society or public officials including the judge himself. The rise of corruption in Indonesia will make foreign investors flee who invest their capital in Indonesia, because investors feel uncomfortable investing in a country full of corruption. Corruption for investors is a factor that can cause harm to them so they choose to withdraw their investments in a country that is corrupt. The basic principles of the Code of Ethics and the Code of Conduct of Judges are implemented in the following ten rules of conduct: (1) Behaving Fairly, (2) Behaving Honestly, (3) Behaving Wisely and Wisely, (4) Being Independent, (5) High Integrity, (6) Responsible, (7) Upholding Self-Esteem, (8) High Discipline, (9) Behaving Humbly, (10) Being Professional